2022
DOI: 10.1038/s41420-021-00804-6
|View full text |Cite
|
Sign up to set email alerts
|

TGF-βRII regulates glucose metabolism in oral cancer-associated fibroblasts via promoting PKM2 nuclear translocation

Abstract: Cancer-associated fibroblasts (CAFs) are highly heterogeneous and differentiated stromal cells that promote tumor progression via remodeling of extracellular matrix, maintenance of stemness, angiogenesis, and modulation of tumor metabolism. Aerobic glycolysis is characterized by an increased uptake of glucose for conversion into lactate under sufficient oxygen conditions, and this metabolic process occurs at the site of energy exchange between CAFs and cancer cells. As a hallmark of cancer, metabolic reprogram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…This demonstrates that IDH3α is a key metabolic switch in CAFs (84). A recent study revealed that TGF-β type II receptor (TGF-βRII) nuclear translocation of PKM2 inhibits glucose metabolism in CAFs, thereby inhibiting oral cancer tumor growth (85).…”
Section: Tgf-β Signaling Pathway Mediates the 'Reverse Warburg Effect...mentioning
confidence: 93%
“…This demonstrates that IDH3α is a key metabolic switch in CAFs (84). A recent study revealed that TGF-β type II receptor (TGF-βRII) nuclear translocation of PKM2 inhibits glucose metabolism in CAFs, thereby inhibiting oral cancer tumor growth (85).…”
Section: Tgf-β Signaling Pathway Mediates the 'Reverse Warburg Effect...mentioning
confidence: 93%
“…In addition, TGF-β treatment decreases the flow of pyruvate to the TCA cycle by directly activating the gene encoding pyruvate dehydrogenase kinase 1 (PDK1), and this enzyme inactivates the TCA cycle enzyme pyruvate dehydrogenase in mouse and human fibroblasts, a human Burkitt’s lymphoma cell line, and human renal cell carcinoma cell lines [ 169 , 170 ]. Our research team successfully separated and cultured human oral CAFs from human cancer [ 156 ], and verified the upregulated glycolysis via PFKFB3 and PKM2 overexpression in oral CAFs [ 157 , 158 ]. However, we found that TGF-βRII was downregulated in oral CAFs and thus promoted PKM2 nuclear translocation via increasing p-ERK1/2, which was responsible for the elevated glycolysis in oral CAFs [ 157 , 171 ].…”
Section: Tgf-β-dependent Metabolism Of Stromal–epithelial Coupling An...mentioning
confidence: 99%
“…Our research team successfully separated and cultured human oral CAFs from human cancer [ 156 ], and verified the upregulated glycolysis via PFKFB3 and PKM2 overexpression in oral CAFs [ 157 , 158 ]. However, we found that TGF-βRII was downregulated in oral CAFs and thus promoted PKM2 nuclear translocation via increasing p-ERK1/2, which was responsible for the elevated glycolysis in oral CAFs [ 157 , 171 ]. This study demonstrates that TGFβRII is reversely correlated with glycolysis via activation of non-canonical TGF-β signaling.…”
Section: Tgf-β-dependent Metabolism Of Stromal–epithelial Coupling An...mentioning
confidence: 99%
“…GlyCAF share similar transcriptional profiles with previously identified myCAF 6 , 45 , 61 , which are driven by TGFβ signaling and implicated in CD8 + T cell exclusion. TGFβ also drives glycolytic metabolism in fibroblasts 62 64 , uncovering a potential role for TGFβ in glyCAF biogenesis, although this warrants further investigation. This work highlights the importance of considering the functional features of CAFs when developing therapeutic strategies targeting the tumor microenvironment 65 .…”
Section: Discussionmentioning
confidence: 99%